Programmed cell death ligand‐1: A dynamic immune checkpoint in cancer therapy. (28th March 2020) - Kalim, Muhammad; Iqbal Khan, Muhammad Saleem; Zhan, Jinbiao
Abstract: Antibody‐based immunotherapies play a pivotal role in cancer research with efficient achievements in tumor suppression. Tumor survival is assisted by modulation of immune checkpoints to create imbalances between immune cells and cancer cell's environment. The modulation results in T‐cell signal inhibition ultimately inert its proliferation and activation against various tumor cells. PD‐L1, a 40 kDa transmembrane protein of B7 family, binds with PD‐1 on the membrane of T cells which results in inhibition of T‐cell proliferation and activation. PD‐L1/PD‐1 pathway has generated novel target sites for antibodies that can block PD‐L1/PD‐1 interactions. The blockage results in T‐cell proliferation and tumor cell suppression. The PD‐L1 immune checkpoint strategies' development, expression and regulations, signal inhibitions, and developmental stages of PD‐L1/PD‐1 antibodies are briefly discussed here in this review. All this information will provide a base for new therapeutic development against PD‐L1 and PD‐1 immune checkpoint interactions and will make available promising treatment options. Abstract : PD‐L1, a 40 kDa transmembrane protein of B7 family, binds with PD‐1 that result in inhibition of T‐cell proliferation and activation. PD‐L1/PD‐1 pathway has generated novel target sites for antibodies that can block PD‐L1/PD‐1 interactions. The blockage results in T‐cell proliferation and tumor cell suppression. The PD‐L1 immune checkpoint strategies' development, expression, and regulations, signals inhibitions, and developmental stages of PD‐L1/PD‐1 antibodies are briefly discussed.